A case report with shock induced by tolvaptan in an elderly patient with congestive heart failure. Issue 1 (January 2018) - Zhang, Zhi-gang; Liu, Xin-min
Abstract: Rationale: Tolvaptan (TLV) is a new vasopressin type 2 receptor antagonist effective in patients with heart failure (HF). Accumulating evidences have revealed that treatment with TLV does not alter the blood pressure significantly. Patient concerns: An 84-year-old man was diagnosed with acute exacerbation of chronic HF due to ischemic cardiomyopathy, arrhythmia, mitral and aortic regurgitation. Treatment with TLV increased the urine volume and improved the dyspnea. After 4 days use of TLV (3.75 mg QD, 7.5 mg QD, 7.5 mg QD, and 15 mg QD, respectively), decrease in blood pressure to less than 90/60 mmHg was observed continuously and the lowest blood pressure was 80/37 mmHg. He was apyretic and felt only thirsty. Central venous pressure was 12 cmH2 O. Diagnoses: Because no other medications were changed and no signs of hypovolemic, septic, allergic, or cardiac shock were detected, we suspected an adverse reaction to TLV. Intervention: Intravenous hydration was performed with 250 mL of normal saline. Outcomes: His blood pressure increased gradually and the statue of hypotention lasted for 14 hours. The dose of TLV was decreased to 7.5 mg/d from the next day to discharge. During this period, his blood pressure was stable at about 125/60 mmHg. Lessons: TLV has side effect of severe hypotension that is consistent with its physiological activity. The dose should be increased gradually to achieve the desired effect, while attention should be paid to potential drug interactions.